Upaya Mengatasi Kesulitan Memahami Bacaan pada Mata Pelajaran Bahasa Indonesia dengan Menggunakan Metode Cooperative Integrated Reading And Composition (CIRC) Studi pada Siswa Kelas IV SD Negeri 38 Rejang Lebong - Margono, Margono (Sekolah Tinggi Agama Islam Negeri (STAIN) Curup, 2017)
From the research that lâve done that in class IV SDN 38 Rejang Lebong about the subject of Bahasa Indonesia still use the old method like speech method, so the understanding the students in reading. The Cooperative Integrated and Reading Composition method for the learning of bahasa Indonesia. This research use classromm action research using descriptive qualitative. The object of the research is the students of class IV SDN 38 Rejang Lebong. The learning process in Bahasa Indonesia using the CIRC model can done in 3 cycles. The result of the research show that the application of CIRC model for the understanding of the material of reading the intensif text can run effectively. The ability to read the understanding of the students are literal understanding, reorganizing and inferensial. The texts that are given to students have been swithched with the SMOG formula. The result of the study in cycle 1 has medium 69,5 and increase in the second cycle become 70 and increase in the third cycle with the medium 70,59. Based on this research can be suggested that this research well preparation and good attension in dividing a group task and avoid mistake in organizing the group and chosing the suitable text for the stidents based on their age.